2017
DOI: 10.1002/ejoc.201700485
|View full text |Cite
|
Sign up to set email alerts
|

Heck‐Like Reactions Involving Heteroatomic Electrophiles

Abstract: Since the discovery of the Heck reaction in the early seventies, this reaction has become a powerful tool in synthetic organic chemistry. By employing heteroatomic instead of traditional carbon electrophiles, the Heck reaction shows an intriguing flexibility. These "hetereoatomic-Heck reactions" reinvigorate the area, offering new routes to highly useful synthetic precursors and structural motifs present in biologically active compounds. This microreview focuses on early developments leading to the heteroatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…Ab road range of functional groups are also compatible with the cyclization, including ethers (6,9,21,23,29), esters (8,33), isolated alkenes (35), aromatic halogens (10)(11)28), trifluoromethyl groups (7), protic functionalities (15-16, 20, 24, 26, 33), and arange of heterocycles (17)(18)(26)(27). Increased substitution on the 5-membered ring, however,i sw ell tolerated (24), as is substitution on the alkyl group (25).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…Ab road range of functional groups are also compatible with the cyclization, including ethers (6,9,21,23,29), esters (8,33), isolated alkenes (35), aromatic halogens (10)(11)28), trifluoromethyl groups (7), protic functionalities (15-16, 20, 24, 26, 33), and arange of heterocycles (17)(18)(26)(27). Increased substitution on the 5-membered ring, however,i sw ell tolerated (24), as is substitution on the alkyl group (25).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Recently,Heck-type cyclizations of nitrogen electrophiles have emerged as ap owerful and flexible strategy for preparing nitrogen-containing heterocycles, [10,11] and we have shown that unsaturated lactams bearing free NÀH groups can be prepared via the palladium-catalyzed cyclization of O-phenyl hydroxamates onto pendant alkenes. [12] We hypothesized that the synthesis of N À Hb earing imidazolidinones from N-phenoxy ureas might also be possible,w hich would allow for the direct synthesis of unprotected imidazolidinone scaffolds bearing unsaturation vicinal to one of the nitrogen centers.H erein, we describe the successful realization of that goal, and report conditions for the preparation of unsaturated, unprotected imidazolidinones using an aza-Heck strategy.U sing easily accessed starting materials,a nd commercially available catalytic components,w es how that the reaction enjoys broad functional group tolerance and is highly flexible with respect to accessible ring topologies.Further,by the addition of iodide additives,i someric dihydroimidazolones can also be prepared from the same starting materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Heck-type cyclizations of nitrogen electrophiles have emerged as a powerful and flexible strategy for preparing nitrogen-containing heterocycles, [10],[11] and we have shown that unsaturated lactams bearing free N–H groups can be prepared via the palladium-catalyzed cyclization of O -phenyl hydroxamates onto pendant alkenes. [12] We hypothesized that the synthesis of N–H bearing imidazolidinones from N -phenoxyureas might also be possible, which would allow for the direct synthesis of unprotected imidazolidinone scaffolds bearing unsaturation vicinal to one of the nitrogen centers.…”
mentioning
confidence: 99%
“…Thes cope of reaction was next investigated (Scheme 2). Themodel substrate 4 was isolated in 84 %yield, and closely related derivatives were prepared with similar efficiency (6)(7)(8)(9)(10)(11). More substituted alkenes,i ncluding tetrasubstituted alkene,also participate well in the reaction (12)(13)(14).…”
mentioning
confidence: 99%